2021
DOI: 10.1186/s12879-021-05927-w
|View full text |Cite
|
Sign up to set email alerts
|

Distorted chemosensory perception and female sex associate with persistent smell and/or taste loss in people with SARS-CoV-2 antibodies: a community based cohort study investigating clinical course and resolution of acute smell and/or taste loss in people with and without SARS-CoV-2 antibodies in London, UK

Abstract: Background Loss of smell and/or taste are cardinal symptoms of COVID-19. ‘Long-COVID’, persistence of symptoms, affects around one fifth of people. However, data regarding the clinical resolution of loss of smell and/or taste are lacking. In this study we assess smell and taste loss resolution at 4–6 week follow-up, aim to identify risk factors for persistent smell loss and describe smell loss as a feature of long-COVID in a community cohort in London with known SARS-CoV-2 IgG/IgM antibody stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 35 publications
4
37
2
1
Order By: Relevance
“…This decline in older age has been observed in other studies, 4,17,18 and may be spurious due to selective competing risk of mortality, non-response bias, lower symptom reporting in older adults, misattribution of long COVID to other illness, or a combination of these factors. The findings that long COVID was 50% higher in women than men is consistent with reports from most 4,17,1922 but not all previous studies. 4,18 We found some evidence of higher long COVID reporting among individuals of white ethnicity and of higher educational attainment, which was unexpected given the common associations of these characteristics with lower morbidity more generally.…”
Section: Discussionsupporting
confidence: 92%
“…This decline in older age has been observed in other studies, 4,17,18 and may be spurious due to selective competing risk of mortality, non-response bias, lower symptom reporting in older adults, misattribution of long COVID to other illness, or a combination of these factors. The findings that long COVID was 50% higher in women than men is consistent with reports from most 4,17,1922 but not all previous studies. 4,18 We found some evidence of higher long COVID reporting among individuals of white ethnicity and of higher educational attainment, which was unexpected given the common associations of these characteristics with lower morbidity more generally.…”
Section: Discussionsupporting
confidence: 92%
“…In addition they also found no association between recovery of smell function and viral load on nasopharyngeal swab testing or COVID-19 severity. Contrarily, Makaronidis et al found in their study of 380 patients (270 female, 110 male) recruited online from a community-based cohort that men were more likely than women (72.8% vs. 51.4%) to fully recover their sense of smell [24] . Age, race, and smoking status were not associated with improved rates of recovery at 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous reports describing rates of smell recovery, very little information exists regarding the factors associated with recovery vs. non-recovery. Few have investigated this phenomenon, and to date almost no clinical, epidemiological, or laboratory markers have been identified [22] , [23] , [24] , [25] . In their study of prospectively recruited patients from 3 European centers, Saussez and colleagues examined patterns of recovery among 288 patients within 60 days of onset of olfactory dysfunction [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory dysfunction has been reported with other coronavirus infections and epidemics, including the SARS-CoV virus [ 53 ], providing precedence for the OD caused by SARS-CoV-2. What’s more, two studies found COVID-19 patients had a longer duration (10 vs. 15 days, p < 0.006) and lower recovery (57.7% vs. 72.1%, p = 0.027) than COVID-19 seronegative patients with olfactory dysfunction, suggesting that OD in COVID-19 has a unique etiology (although false negatives could complicate these results) [ 54 , 55 ]. Therefore, while the exact etiology is unclear, it is likely that SARS-CoV-2 produces sensory impairment irrespective of other upper respiratory symptoms.…”
Section: Main Textmentioning
confidence: 99%
“…Sex and age differences have been reported, with some studies observing a higher incidence ( p < 0.011) [ 50 ] and longer duration (26 vs. 14 days, p = 0.009) of OD in females than males, including higher persistence at 4–6-week follow-up (OR 2.46, 95% CI 1.46–4.13, p = 0.001) [ 49 , 55 ]. Conversely, Amer and colleagues noted that females had better recovery at 1 month from COVID-19 onset (83.9% vs. 62.5%, p < 0.005), proposing elevated androgens in males that enhance transcription of TMPRSS2 [ 56 ].…”
Section: Main Textmentioning
confidence: 99%